Experimental and Theoretical Investigations on Progressive Collapse Resistance of the Concrete-Filled Square Steel Tubular Column and Steel Beam Frame under the Middle Column Failure Scenario - Wei Xuan; Lai Wang; Changjiang Liu; Guoqi Xing; Lili Zhang; Haitao Chen (Shock and Vibration)
A static loading test was carried out on a 1/3-scale concrete-filled square steel tubular column-steel beam frame (CFSTSBF) specimen with 2 spans to study its progressive collapse behaviors under the middle column failure scenario using the alternate load path method and to examine the failure mode and load transfer and main resistance mechanisms of the residual structure. Then, theoretical models of the specimen, involving the whole collapse process, were developed, and the resistance and deformation relationships of each model were calculated and validated with test results. The results indicated that the specimen collapse process includes the elastoplastic stage, plastic stage, transfer stage, and catenary stage, the beam mechanism and catenary mechanism were the principal mechanisms for the structure against progressive collapse, and catenary action can significantly strengthen structural resistance. The modified theoretical models with higher practical accuracy could be used to assess structural performances against progressive collapse.